Analysis of interior rotor for high-speed brushless DC motor using finite element method - Abdullah, Nurfaezah; Karim, Kasrul Abdul; Othman, Raja Nor Firdaus Raja; Jidin, Auzani; Sutikno, Tole (International Journal of Power Electronics and Drive Systems (IJPEDS), 2023)
The permanent magnet of brushless DC (BLDC) motor is ideally suited for high-speed application due to its superior performance and efficient as compared to other types of electrical motors. However, to operate in high-speed operation, the rotors that hold the magnet must be able to withstand high centrifugal force. Due to that, the main objective of this project is to design and develop the suitable rotor for high-speed BLDC motor through the finite element method (FEM) Ansys Maxwell modeling software. In addition, this project is also carried out to determine the ability of the modeled software to reach the high-speed performances in terms of cogging torque and induce voltage. In this project, the selected BLDC motor was fabricated and measured experimentally. The result showed that the designed rotor can achieve speed of almost 14,500 rpm.